A Case of Unresectable Rectal Necrosis - Mohammed Nassif; Ahmed Ameer; Sarkis H. Meterissian; Ari-Nareg Meguerditchian (Case Reports in Medicine)
Introduction. Necrosis of the rectum is an uncommon finding due to abundant collateral vasculature. Its management remains challenging, without clear consensus in the literature. Case Report. We describe a case of a 53-year-old woman with multiple medical comorbidities that presented in septic shock and hematochezia. Colonoscopy revealed ischemic colitis. Conservative management was instituted. At two weeks, she presented evidence of peritonitis. Exploratory laparotomy revealed extensive necrosis of the left colon and rectum. Due to dense inflammation, resection was deemed unsafe. Therefore, a transverse ostomy with mucosal fistula was preformed. Multiple drains were left in place. The patient healed uneventfully. Conclusion. This case illustrates that, if extensive dissection of the distal colon and rectum is unsafe due to the patient's critical condition or technical feasibility, then a diverting ostomy of the proximal viable bowel along with a mucus fistula and good drainage of the abdomen represents an acceptable alternative.